2021
DOI: 10.3389/fpls.2021.734430
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Root Physiological Parameters and Potassium and Calcium Currents in the Rhizoplane of the Apple Rootstock Superior Line 12-2 With Improved Apple Replant Disease Resistance

Abstract: The cultivation of resistant rootstocks is one of the more effective ways to mitigate apple replant disease (ARD). We performed an ion current test, a pot experiment, and a pathogen infection test on the apple rootstocks 12-2 (self-named), T337, and M26. The ion current test showed that exposure to ARD soil extract for 30 min had a significant effect on K+ ion currents at the meristem, elongation, and mature zones of the M26 rhizoplane and on Ca2+ currents in the meristem and elongation zones. ARD also had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Semi-quantitative RT-PCR detection and qRT-PCR analysis showed that the 8 potassium channel genes may participate in rhizosphere K + homeostasis of 12-2 by responding to ARD stress. These results also help to explain our previous findings on ion currents in 12-2 roots (Mao et al, 2021b). A study by Fuchs et al (2005) showed that the K + channel gene OsAKT1 regulated the absorption of K + to improve rice salt tolerance, and a study by Jin et al (2017) showed that ion channels could increase plant drought resistance through K + efflux.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Semi-quantitative RT-PCR detection and qRT-PCR analysis showed that the 8 potassium channel genes may participate in rhizosphere K + homeostasis of 12-2 by responding to ARD stress. These results also help to explain our previous findings on ion currents in 12-2 roots (Mao et al, 2021b). A study by Fuchs et al (2005) showed that the K + channel gene OsAKT1 regulated the absorption of K + to improve rice salt tolerance, and a study by Jin et al (2017) showed that ion channels could increase plant drought resistance through K + efflux.…”
Section: Discussionsupporting
confidence: 71%
“…In mid-November 2021, one hundred 12-2 seedlings of similar size with 4-5 leaves were transplanted into black plastic pots (7.0 cm × 5.0 cm × 8.5 cm) filled with sterile substrate after seedling acclimatization. The specialized Fusarium proliferatum strain MR5 (MW600437.1) associated with ARD was recently screened and identified (in review); it is highly pathogenic to apple roots (Mao et al, 2021b) and was discovered by the research group of Professor Mao Zhiquan of Shandong Agricultural University. On November 24, a layer of pathogenic fungi was inoculated in liquid potato dextrose medium (PDB, Haibo, Qingdao, Shandong, China), cultured for 7 days, and then filtered through 8 layers of sterile gauze to obtain a spore suspension.…”
Section: Plant Materials and Experimental Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a new line of Malus species that has not been identified previously. In our previous research, ARD had significant effects on several parameters of M.9T337 and M.26 rootstocks, but had no significant effect on 12-2 [16,17]. On this basis, we used 12-2 and PYTC as control, planted in an ARD orchard as experimental rootstock materials and grafted them with 13 apple varieties, including Fuji 2001 and Tianhong 2.…”
Section: Introductionmentioning
confidence: 99%